IMPLEMENTASI PROGRAM PENANGGULANGAN TUBERKULOSIS DI PUSKESMAS KAMPUNG DALAM KOTA PONTIANAK - Aboy E.21108002 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Tuberklosis (TB) remains a major public health problem in Indonesia. In an effort to eradicate TB defined morbidity, mortality and transmission of TB control in accordance with the vision. This study focused on the organization, interpretation, and application. Foci are discussed with qualitative methods and case studies in the health center in the village of East Pontianak District. From the research it was found that the organizations implementing TB control program has been run in accordance with the procedure but can not walk well and reports required by the manager has not produced complete. As for the aspect in the interpretation of the TB control program in the clinic most nurses do not fully understand TB control procedures because they lack training. In applying the TB control program is still lacking. Therefore, the researchers recommend that the organization's focus on performance evaluation by the head of health center physicians to conduct TB diagnosis. As for the suggestion to focus interpretation to apply sanctions to officials who do not do their job properly. As for the suggestion to focus on the application to add a number of special officers involved in the TB control program. Keywords: Implementation of Tuberculosis Control Program, Health Center